2013
DOI: 10.1007/s00441-013-1752-1
|View full text |Cite
|
Sign up to set email alerts
|

NT5E and FcGBP as key regulators of TGF-1-induced epithelial–mesenchymal transition (EMT) are associated with tumor progression and survival of patients with gallbladder cancer

Abstract: Epithelial–mesenchymal transitions (EMTs) are essential manifestations of epithelial cell plasticity during tumor progression. Transforming growth factor-β(TGF-β) modulates epithelial plasticity in tumor physiological contexts by inducing EMT, which is associated with the altered expression of genes. In the present study, we used DNA micro-array analysis to search for differentially expressed genes in the TGF-β1 induced gallbladder carcinoma cell line (GBC-SD cells), as compared with normal GBC-SD cells. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 24 publications
6
98
0
Order By: Relevance
“…Our study is thus consistent with recent reports that in the tumor microenvironment, CAFs are important regulators of tumor immunity (38). Another finding of our study is the observation that CD73 gene expression is strongly correlated with an EMT gene signature, consistent with a recent study in gallbladder cancer cells (18). CD73 has been shown to be upregulated on human mammary epithelial cells stably expressing the EMT-inducers Twist, Snail, or TGFb1 (39).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study is thus consistent with recent reports that in the tumor microenvironment, CAFs are important regulators of tumor immunity (38). Another finding of our study is the observation that CD73 gene expression is strongly correlated with an EMT gene signature, consistent with a recent study in gallbladder cancer cells (18). CD73 has been shown to be upregulated on human mammary epithelial cells stably expressing the EMT-inducers Twist, Snail, or TGFb1 (39).…”
Section: Discussionsupporting
confidence: 93%
“…Others have shown that in vitro treatment of alloantigenprimed human T cells with an anti-CD73 mAb enhances T-cell cytotoxicity against human ovarian cancer cells (16). CD73 overexpression has been associated with worse clinical outcomes in different types of cancer (15,(17)(18)(19). In triple negative breast cancer, high levels of CD73 gene expression are associated with poor prognosis and resistance to immunogeniccell death induced by anthracyclines (15).…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, TGF-β is one of the most powerful inducers of EMT; for example, in a gallbladder carcinoma cell line it promotes a mesenchymal phenotype with a notorious increase in the expression of ectonucleotidase CD73, the enzyme that dephosphorylates AMP to adenosine, suggesting that the nucleoside could be fundamental in the EMT induction program activated by TGF-β in this cell line [93]. However, CD73 has been part of a polemic argument regarding its involvement in the cancerous process.…”
Section: Adora2amentioning
confidence: 70%
“…According to the UCSC Genome Browser and Database of Genomic Variants [25,26], this duplicated region is located within the FCGBP gene. Characterized by the production of a large (encoded by a 17-kb mRNA) mucin-like protein that binds the Fc portion of IgG molecules, this gene has been reported as differentially expressed in gallbladder [45], prostate [46], thyroid [47], lung [48], colon [49], and ovarian cancer [50]. Present in serum, the protein can be found in higher levels in patients with autoimmune diseases [51].…”
Section: Discussionmentioning
confidence: 99%